ELECTROMAGNETIC FILLING ON THE TERRITORY, CREATED BY USER'S STATIONS OF CELLULAR COMMUNICATIONS - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The equations defining the relationship of terrestrial electromagnetic filling created by mobile user's stations of cellular communications, with the total intensity of an electromagnetic background created by these stations at a terrestrial surface, and also with probability of excess of the maximum permissible level by cumulative intensity of electromagnetic fields generated by user's and base stations of cellular communications are given. The equations for an estimation of maximum permissible level of terrestrial electromagnetic filling created by user's stations at which the probability of excess of the given maximum permissible level of field intensity in a considered observation point by cumulative intensity of electromagnetic fields generated by user's and base stations of cellular communications in presence of an external electromagnetic background, is admissible, are resulted.